Higher Non-processed Red Meat Consumption Is Associated With a Reduced Risk of Central Nervous System Demyelination - Black, L; Bowe, G; Pereira, G; Lucas, R; Dear, K; van Der Mei, I; Sherriff, J; Ausimmune Investigator Group (Frontiers Media, 2019)
The evidence associating red meat consumption and risk of multiple sclerosis is inconclusive. We tested associations between red meat consumption and risk of a first clinical diagnosis of central nervous system demyelination (FCD), often presaging a diagnosis of multiple sclerosis. We used food frequency questionnaire data from the 2003-2006 Ausimmune Study, an incident, matched, case-control study examining environmental risk factors for FCD. We calculated non-processed and processed red meat density (g/1,000 kcal/day). Conditional logistic regression models (with participants matched on age, sex, and study region) were used to estimate odds ratios (ORs), 95% confidence intervals (95% CI) and p-values for associations between non-processed (n = 689, 250 cases, 439 controls) and processed (n = 683, 248 cases, 435 controls) red meat density and risk of FCD. Models were adjusted for history of infectious mononucleosis, serum 25-hydroxyvitamin D concentrations, smoking, race, education, body mass index and dietary misreporting. A one standard deviation increase in non-processed red meat density (22 g/1,000 kcal/day) was associated with a 19% reduced risk of FCD (AOR = 0.81; 95%CI 0.68, 0.97; p = 0.02). When stratified by sex, higher non-processed red meat density (per 22 g/1,000 kcal/day) was associated with a 26% reduced risk of FCD in females (n = 519; AOR = 0.74; 95%CI 0.60, 0.92; p = 0.01). There was no statistically significant association between non-processed red meat density and risk of FCD in males (n = 170). We found no statistically significant association between processed red meat density and risk of FCD. Further investigation is warranted to understand the important components of a diet that includes non-processed red meat for lower FCD risk.